2012
DOI: 10.1111/j.1468-5906.2012.01678.x
|View full text |Cite|
|
Sign up to set email alerts
|

Ethnodoxy: How Popular Ideologies Fuse Religious and Ethnic Identities

Abstract: REFERENCE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 22 publications
2
28
0
1
Order By: Relevance
“…This conflation ignores the evolution of a wide variety of expressions and forms of Islam (Westerlund & Svangberg, 1999) among diverse groups including large non-Arab Muslim populations in several countries (Baker, 2012;Hoveyda, 2005) as well as the existence of significant non-Muslim Arab populations (as in Egypt, Lebanon, and Syria) and non-Arab Muslim majorities in countries such as Malaysia and Indonesia (Mohammed, 2011). Karpov, Lisovskaya, and Barry (2012) analyzed the conflation of religion and ethnicity in terms of ethnodoxy or ''ideology that rigidly links a group's ethnic identity to its dominant faith'' (p. 639), which fuels essentialism and prejudice because group members are ''presumed as belonging to that faith regardless of their actual individual beliefs or practices'' (p. 641). Fadda-Conrey (2011) further suggested that the logic of using either religious or ethnic markers to determine ''the American from the unAmerican'' leads to widespread (often misdirected) suspicion, paranoia and the perception of threat (p. 535).…”
Section: Arab=muslim Conflationmentioning
confidence: 99%
“…This conflation ignores the evolution of a wide variety of expressions and forms of Islam (Westerlund & Svangberg, 1999) among diverse groups including large non-Arab Muslim populations in several countries (Baker, 2012;Hoveyda, 2005) as well as the existence of significant non-Muslim Arab populations (as in Egypt, Lebanon, and Syria) and non-Arab Muslim majorities in countries such as Malaysia and Indonesia (Mohammed, 2011). Karpov, Lisovskaya, and Barry (2012) analyzed the conflation of religion and ethnicity in terms of ethnodoxy or ''ideology that rigidly links a group's ethnic identity to its dominant faith'' (p. 639), which fuels essentialism and prejudice because group members are ''presumed as belonging to that faith regardless of their actual individual beliefs or practices'' (p. 641). Fadda-Conrey (2011) further suggested that the logic of using either religious or ethnic markers to determine ''the American from the unAmerican'' leads to widespread (often misdirected) suspicion, paranoia and the perception of threat (p. 535).…”
Section: Arab=muslim Conflationmentioning
confidence: 99%
“…Во многих социологических работах подчеркивается, что для таких православных религиозная идентичность заменяет этническую либо национальную идентичность [Зоркая, 2009; Куперман, Сайгал, Шиллер, 2017; Филатов, Лункин, 2005; Фурман, Каариайнен, 2007]. Исследования показывают, что этническая и национальная идентичность действительно тесно переплетены с религиозной идентичностью [Куперман, Сайгал, Шиллер, 2017;Karpov, Lisovskaya, Barry, 2012], однако выявляемая статистическая взаимосвязь между этими феноменами не может быть достаточным основанием для утвержде-ния, что если человека нельзя причислить к высокорелигиозной группе, то помимо этнической идентичности за причислением себя к тому или иному вероисповеда-нию более ничего не стоит. Так, подавляющая часть православных верит в Бога, заметная часть участвует в религиозных практиках хотя бы изредка.…”
Section: е в пруцкова представляем исследованиеunclassified
“…On the first of these points, Irina Papkova notes that fundamentalist groups that have taken leading roles in political activism are 'decidedly lay in character', but nonetheless it is these fundamentalists who 'come closest to fitting the parameters usually associated by Western observers with the political platform of the church as a whole ' (2011, 65-66). The second key point -that political Orthodoxy has a well-developed ideologically focused literature supporting it-serves to distinguish the political Orthodox from the large majority of what I called above, following Karpov, Lisovskaya, and Barry (2012), ethnodox believers.…”
Section: Reflexive Religio-nationalism-ethnodoxymentioning
confidence: 99%
“…Such a notion does not demand detailed justification, but stems from selfidentification drawing primarily on history and culture, ethnicity and territoriality. Karpov, Lisovskaya, and Barry (2012) (2003,(28)(29). Within reasoned religionationalism I distinguish two distinct strands-the nationalist ex patria strand, and the faith-based ex religio strand.…”
mentioning
confidence: 99%